META-ANALYSIS OF THE EFFECT OF CROSSWORD PUZZLE MEDIA TO LEARNING AND STUDENTS’ SOCIAL SCIENCE LEARNING OUTCOME IN ELEMENTARY SCHOOL - Fidrayani Fidrayani; Rusni Deden Purdiasih (JIP Jurnal Ilmiah PGMI, 2022)
This study aims to analyze the effect of crossword puzzle learning media on learning and social science learning outcomes of elementary school students. The research method practiced is a meta-analysis by describing the results of the analysis of various studies, in various schools in Indonesia, which have been published nationally. The sample is ten articles that have been published in accredited national journals from 2014 to 2019. The writing instrument is in the form of a coding sheet containing data and information on research findings in each article. Based on the analysis, the average size effect of crossword puzzles on learning and overall Social Science learning outcomes is 1.49 which is included in the high category of effectiveness. The average value of crossword puzzles effect on social science learning outcomes based on the dependent variable is 2.25 which is also included in the high category. This fact denotes that crossword puzzles are effective in teaching Social Sciences on any material, and have an effect on decent student learning outcomes.